(3aJM QH GdHQjI HTQM GdbUjOI GdNRQLjIs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3YHO Gddg Hf eMeO Hf YHO Gddg GdNRQLj GdeGdcj, Rcj GdOjfs ((3eMeO Hf GdMSjf GdchQGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi hVY Yde GdYQhV djYQa Hg ChRGf GdefXhe hHYO agPG TQM Ydi GdNRQLjI GdefXheI Ydi HMQ GdWhjd ai Yde GdYQhV hGdbhGai ai fXe GdYdGeI VjGA GdOjf CHj eMeO GdNRQLi jMd CdaGXgG s
(3BNQgG (B:s
(3hai fSNI JhSW ai PG GdYde Ci Yde GdYQhV GdeJHhY HYde GdbhGai hGdYjhH JhSYg Ci JRjOg hGdMeO ddg hMOg hUdi Gddg hSde Ydi ef dGfHi HYOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdYQhV hGdbhGais